Green supply chain initiatives among certified companies in Malaysia and environmental sustainability: Investigating the outcomes - Eltayeb, Tarig K.; Zailani, Suhaiza; Ramayah, T. (Resources, conservation and recycling, 2011)
The relationship between green supply chain initiatives and performance outcomes has been subject to numerous studies but the results are not conclusive. This study tries to assess the actual environmental, economic and intangible outcomes resulting from the adoption of green supply chain initiatives. This study used a structured questionnaire derived from the literature and employing a mail survey to collect responses form a group of 569 ISO 14001 certified firms in Malaysia. The results of testing the hypotheses that predicted that green supply chain initiatives have positive effect on the outcomes showed that eco-design have significant positive effect on the four types of outcomes (environmental outcomes, economic outcomes, cost reductions, and intangible outcomes). Reverse logistics was found to have significant positive effect on cost reductions only. However, green purchasing was not found to have significant effect on any of the four types of outcome. Through designing environmentally friendly products and taking back products and packaging, business organizations can generate benefits to the environment, in the form of reduced waste and better resource utilization, in addition to economic benefits and cost reductions to the organizations.